Uji Kualitas Kompos Feses Ayam Petelur Berdasarkan Variasi Dosis Probiotik Dan Lama Pengomposan - Supriatna, Ucup; Somanjaya, Rachmat; Imanudin, Oki (Tropical Livestock Science Journal, 2025)
This research was carried out from July 30 to September 2 2024. This research aims to test the quality of laying chicken feses compost based on variations in probiotic dosage and composting time. The variations in probiotic doses used were 0%, 5%, 10%, and 15%, with composting times of 14, 21, and 28 days. This research used a Completely Randomized Design (CRD) method with a 4 x 3 factorial pattern, namely four levels of probiotic dosage and three levels of composting time, with each treatment combination repeated three times. The data obtained were analyzed using the General Linear Model and continued with the Tukey test to determine differences between treatments at the 5% level. The parameters measured include nitrogen (N), phosphorus (P), potassium (K), and composting temperature. The results showed that the addition of probiotics and composting time had a significant effect on compost quality (P<0.05). The interaction between probiotic dose and composting time did not have a significant impact. A 10% probiotic dose produced the highest nitrogen (1.33%) and phosphorus (0.37%) content on day 28, which meets compost quality standards based on the Indonesian National Standard (SNI). The highest potassium content (2.17%) was found at a 5% probiotic dose on day 28. Composting temperature reached its peak on day 21, with the highest temperature in the 5% probiotic treatment (36°C). The conclusion from this research is that a 10% probiotic dose with a composting time of 28 days is an ideal combination to produce high quality laying hen feses compost.